Clinical Effects of Shenqi Fuzheng Injection in the Neoadjuvant Chemotherapy for Local Advanced Breast Cancer and the Effects on T-lymphocyte Subsets - 代志军 王西京 康华峰 纪宗正 刘蕾 刘小旭 宋玲琴 闵卫利 马小斌 (Journal of Traditional Chinese Medicine, 2008)
Objective： To evaluate clinical effects of Shenqi Fuzheng Injection （参芪抉正注射液） in the neoadjuvant chemotherapy for local advanced breast cancer and the effects on T-lymphocyte subsets. Methods： During the period from 2000 to 2005, 126 patients with local advanced breast cancer were treated with the neoadjuvant chemotherapy. They were randomly divided into the following two groups： a control group of 61 cases treated by chemotherapy alone and a study group of 65 cases treated by chemotherapy plus Shenqi Fuzheng Injection, All the cases of both groups were given the CEF （CTX 500 mg/m^2, d1, 8; EP140 mg/m^2, d1, 8; and 5-Fu 500 mg/m^2, d1,8） regimen. The clinical effects, the effects on T-lymphocyte subgroup and NK cells, and the toxic side effects were observed. Results： All the patients completed two cycles of the chemotherapy, and the efficacy and the toxic side effects were evaluated. For the primary tumor in the breast, the total effective rate was 69.2% （45/65） in the study group and 49.2% （30/61） in the control group with a statistically significant difference in the intergroup comparison （x^2=5.251, P=0.022, 〈 0.05）. There was no progression of the disease in both the groups, and there were no grade IV toxic side effects in the two groups. The major toxic responses were myelosuppression and gastrointestinal reaction, which were milder in the study group than the control group, and with a shorter recovery course in the former than the latter. Besides, an obvious rise of the T-lymphocyte subgroup and NK cells was found in the study group after the neoadjuvant chemotherapy, with a very significant difference from the controls （P〈0.01）. Conclusions： Shenqi Fuzheng Injection can improve and regulate immune function of the patients with local advanced breast cancer given the neoadjuvant chemotherapy, and therefore it can enhance the curative effect and reduce the side effect as well.